Memupuk Kecerdasan Anak Melalui Parenting Sesuai Dengan Minat dan Bakat di TKQ Nur Insani Kotamadya Medan - Tampubolon, Rhoni Ilham (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This service is carried out with the aim of fostering children's intelligence through parenting where parenting is a very important thing to do by school institutions to provide knowledge to parents/guardians of students related to education for early childhood. The purpose of this parenting activity is to provide understanding and guidance to parents/guardians of students on how to foster children's intelligence according to their interests and talents. The method of activity carried out is participatory, namely an effort to provide information to parents/guardians of students and teachers so that they have an increased understanding of the material presented. The form of community service activities is in the form of seminars and interactive discussions related to the intelligence of each child and how to foster that intelligence according to the child's interests and talents. The results of this activity are the implementation of parenting activities for parents/guardians of students at TKQ Nur Insani in fostering children's intelligence according to their interests and talents properly, as well as an increase in the understanding of parents/guardians of students regarding how to foster children's intelligence according to their interests and talents.